2016
DOI: 10.1371/journal.pone.0165711
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Influenza A H1N1pdm09 Virus and Severe Outcomes: A Reason for Broader Vaccination in Non-Elderly, At-Risk People

Abstract: BackgroundRecent pandemics of influenza A H1N1pdm09 virus have caused severe illness, especially in young people. Very few studies on influenza A H1N1pdm09 in post-pandemic periods exist, and there is no information on the severity of both seasonal influenza A(H1N1) and A(H3N2) from the same season, adjusting for potential confounders, including vaccine.Methods and ResultsWe performed a retrospective observational study of adults hospitalized during the 2014 season with influenza A(H1N1) or A(H3N2). All patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 44 publications
(73 reference statements)
5
19
0
Order By: Relevance
“…In 2015, patients with A/H1 outnumbered those with Epidemiology and Infection 5 . This is consistent with previous studies that have shown that A/H1 has, since 2009, remained the dominant cause of clinically severe influenza, particularly in younger adults [3][4][5][6]29], even though A/H3 was the dominant subtype causing hospital admission. In previous influenza pandemics, the pandemic strain has been associated with a high proportion of deaths in patients under 65 years, which continues, albeit at lower proportions, in the decade following the pandemic [30].…”
Section: Discussionsupporting
confidence: 93%
“…In 2015, patients with A/H1 outnumbered those with Epidemiology and Infection 5 . This is consistent with previous studies that have shown that A/H1 has, since 2009, remained the dominant cause of clinically severe influenza, particularly in younger adults [3][4][5][6]29], even though A/H3 was the dominant subtype causing hospital admission. In previous influenza pandemics, the pandemic strain has been associated with a high proportion of deaths in patients under 65 years, which continues, albeit at lower proportions, in the decade following the pandemic [30].…”
Section: Discussionsupporting
confidence: 93%
“…In general, the A(H1N1)pmd09 strain affected young persons more than those older than 50 years, a pattern seen world-wide. Younger age groups and older adults should be the targeted for vaccination [33]. A prospective study in Nicaragua documented high incidence of influenza, especially in infants 6–11 months, a vaccine eligible age [12].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies evaluated risk factors for severe influenza during the 2009 H1N1 influenza pandemic. Adult ICU patients with influenza A(H1N1)pdm09 virus infection were primarily non-elderly, were obese [24][25][26][27][28], and had higher odds of death, invasive mechanical ventilation, acute respiratory distress syndrome (ARDS), septic shock, and multi-lobar pneumonia when compared with seasonal influenza patients [24,29]. In children, independent risk factors for influenza A(H1N1)pdm09-related mortality included chronic neurologic condition or immune compromise, acute myocarditis or encephalitis, and early presumed MRSA co-infection of the lung [30].…”
Section: Risk Factorsmentioning
confidence: 99%